(untitled) (Citizenship in Action: Extension and Culture Magazine, 2023)
Gender inequality is still a phenomenon that is part of different social segments. Even over the years, the man continues to be seen as the main provider of the house while the woman does not need -or should not- study, earn her money and have her independence, being assigned to take care of the house, the children and be totally submissive. The present work has as its theme Gender inequality in the on-site occupational safety course at the IFPB-Campus Patos: a history of the presence of women over the years (2009-2020). An exploratory and quantitative research was developed with data from courses integrated to high school and higher education collected through the academic control sector of the IFPB-Campus Patos. With this, it was discovered that the presence of women proved to be elusive in the Occupational Safety Technologist course until the year 2016 and only from 2017 onwards, the students who did not complete the course maintained a relationship of continuity, standing out in relation to to evasions. In the Occupational Safety Technician course, female participation stands out from the periods that have already ended to those that are still active.